2023
DOI: 10.1039/d2tc04420j
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared emission of a novel nonconventional luminophore for in vitro imaging

Abstract: Luminogens without recognizable luminophores are attracting increasing attention owing to their particular photophysical properties and outstanding biocompatibility features. Despite the rapid advance, it is still a formidable challenge to synthesize...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…These observations suggest the formation of new chromophores in PMV‐LA, which may be attributed to the introduction of electron‐rich atoms in the anhydride group, facilitating TSI of subgroups. [ 12 ] Considering that most CLgens emit in the blue region, this amide reaction could serve as a new approach to realize the red emission of maleic anhydride copolymers.…”
Section: Resultsmentioning
confidence: 99%
“…These observations suggest the formation of new chromophores in PMV‐LA, which may be attributed to the introduction of electron‐rich atoms in the anhydride group, facilitating TSI of subgroups. [ 12 ] Considering that most CLgens emit in the blue region, this amide reaction could serve as a new approach to realize the red emission of maleic anhydride copolymers.…”
Section: Resultsmentioning
confidence: 99%
“…[25][26][27] In particular, Liu et al revealed the relationship between the crystal field intensities of Ce 3+ and Cr 3+ , that is, when Ce 3+ is located in a weak crystal field, the emission of Cr 3+ will also produce broadband emission due to its presence in the weak crystal field. 28 And the absorption bands of Cr 3+ doped NIR phosphors are mostly located in the blue-green light region, which means that Ce 3+ is an excellent sensitizer for Cr 3+ activated broadband NIR phosphors. Wu et al co-doped Ce 3+ into Ca 2 LuHf 2 Al 3 O 12 :Cr 3+ to increase the emission intensity of Cr 3+ by three times through energy transfer from Ce 3+ to Cr 3+ .…”
Section: Introductionmentioning
confidence: 98%
“…Traditional light sources, such as tungsten-halogen lamps, can meet the demands of the broadband emission, but they are large in volume, poor in efficiency and short in lifetime, which limits their practical utilization. 7 NIR LEDs can overcome the above disadvantages, but their applications are restricted by the relatively narrow FWHM (o50 nm). 8 NIR pc-LEDs, fabricated using blue LEDs to excite NIR phosphors, are considered as the ideal NIR light source as they have the merits of a minor environmental impact, compactness, and energy saving.…”
Section: Introductionmentioning
confidence: 99%